A novel three-dimensionally ordered macroporous aerogel for capturing radioactive gaseous iodine. Issue 23 (1st December 2022) - Chang, Sen; Wang, Kunjun; Li, Yongguo; Wang, Jia; Song, Xuemei; Zhang, Zhaochen; Chen, Xin; Pei, Jianlu; Shi, Yunfeng; Luan, Xin'gang
Abstract: To further improve the adsorption capacity of radioiodine in nuclear industry waste gas, the sol-gel combined with colloidal crystal template method was used to successfully introduce a three-dimensionally ordered macroporous (3DOM) structure into the silver-silica aerogel. The effects of the 3DOM structure on the micropore surface area, phase composition, iodine capture capacity and regeneration performance of the aerogels were studied. The results show that the 3DOM structure can effectively increase the micropore surface area of silver-silica aerogel, avoid the agglomeration and grain growth of active components silver, and significantly improve the iodine capture capacity. It will lay the foundation for the application of this new material in the capture of radioactive iodine in the future.